RANCANG BANGUN SISTEM INFORMASI E-ARSIP BERBASIS WEBSITE UNTUK PENGAMANAN DOKUMEN MENGGUNAKAN METODE ADVANCE ENCRYPTION STANDARD (AES) DKPP KOTA SURABAYA - Dio Rachma Putra; Mochamad Sidqon (Yayasan Nuraini Ibrahim Mandiri, 2024)
This study aims to design and implement a website-based e-archive information system by applying the Advance Encryption Standard (AES) method at the Surabaya City Food Security and Agriculture Office (DKPP). The research method uses a waterfall model which consists of the stages of needs analysis, system design, system development, system testing, system implementation, system maintenance, and system evaluation. The e-archive information system is designed to overcome the problem of conventional archive management at DKPP Surabaya which is considered less efficient. The results of the research are in the form of a website-based e-archive information system that facilitates the process of archiving, storing, searching, and downloading archive data for DKPP Surabaya employees. The information system has been tested using blackbox testing to ensure system functionality in accordance with specifications and user needs. This research is expected to increase effectiveness and efficiency in archive management at DKPP Surabaya City. The documents stored in the system are secured using a document security method with the Advance Encryption Standard (AES) method, so that archive data remains secure as long as it is stored and transmitted over the network.The final results of testing this application obtained the results of the encryption process on average document size 1148.977 KB, length of process time 0.19535 seconds and the results of the decryption process on average document size 646.177 KB, length of process time 0.19535 seconds.